Human robot interaction of NAO robot for autism therapeutic purposes - Ho, Swee Tim. (2012)
Children diagnosed with Autism Spectrum Disorder (ASD) are rising each year and it is reported that 216 new cases related to ASD are diagnosed in Singapore. The trend continues to grow as more parents are aware of ASD early signs and symptoms on their child and they sent their child for early diagnosis which helps the child to adjust to the society faster. It is important to discover new ways to treat child with ASD effectively. Advancement in robotics has given the possibilities to use robot as an intervention tool in autism therapy session. In addition, this report investigates the current development of human robot interaction using machines or robot and virtual technologies for autism therapeutic or diagnostics purposes. A collaboration project between Nanyang Technological University technologists and psychologists from Child Guidance Clinic (CGC) is initiated to explore the capabilities of a commercial humanoid, NAO and to develop social behaviours for the robot for autism therapy session. The first technology developed is based on Behaviour-based Interaction Architecture (BIA). However, limitations and drawbacks of the technology are found during mock trials with the psychologists. Furthermore, an improved version that focuses on social interaction which will be remotely controlled by a therapist using Emotions, Behaviours, and Audio Real Time (EBART) interface to interact with the autistic child. EBART interface emphasizes in four essentials modules such as conversational skills, social requesting, initiating social interaction and empathy. In addition, controlling NAO robot motions using Kinect sensor is tested. However, it was not robust because the precisions of the data obtain from the sensor is low and high noise is detected from Kinect. Finally, clinical trials are planned and to be carried out in June to evaluate the viabilities of using NAO as an intervention tool for autism therapy session. As human subject is involved in this experiment, approval from the Institutional Review Board (IRB) is obtained to ensure the welfares and the rights of the participants are protected. The sample size, the therapy setup and the procedure are sent for reviewed and approval by IRB before the clinical trial begins.